Influence of environment, predisposing, enabling and need variables on personal health choices of adults with intellectual disability. - MCCARRON, MARY; MCCALLION, PHILIP; CARROLL, RACHEL; BURKE, EILISH; MCGLINCHEY, EIMEAR (My University, 2013)
Attention to disease and risk factor management is increasingly a feature of people with intellec- tual disability (ID) as an augmented life expec- tancy also exposes a growing number of age- related diseases. An additional concern is little attention to date to physical activity, nutrition, access to social support and other personal health choices and to environmental issues such as the impact of access to social support and the implications of individual?s living ar- rangements. Method: Using a sample of 753 persons with ID from the intellectual disability supplement to the Irish longitudinal study on ageing (IDS-TILDA), forty three variables were grouped into environmental, predisposing, ena- bling, need and personal health choices clusters and hierarchical ordinary least squares regres- sion examined the contribution of environmental, enabling, predisposing, need and all combina- tions of the sets of variables to personal health choices. Findings: Almost 32% of variance was explained primarily by need variables. Most sig- nificant relationships were with meeting up with family and friends (environmental), age, rating of health and worries about getting older (predis- posing), having public health insurance and nursing who come into the home (enabling) and presence of stroke, chronic constipation, func- tional limitations, high assistance needs with activities of daily living (need). Discussion: Taken together, the groupings of variables from the Anderson Model explained a modest amount of variance in the pursuit of positive personal health choices by people with ID. More work is clearly needed in developing evidence-based in- terventions and strategies, and in understand- ing the relationship between positive personal health choices of people with ID and health out- comes.
PUBLISHED
Keywords: Personal Health Choices; Ageing